The Right to Strike and the "Deadweight" of the Common Law - McCrystal, Shae (Victoria University of Wellington Law Review, 2019)
The hostility of the common law in respect of collective action by workers in the form of strikes is notorious. To provide workers with a right to strike, legislative intervention is necessary. In New Zealand and Australia, legislative enactment of the right to strike has taken the form of the "immunity approach" whereby strike action which meets the prerequisites for protection under the relevant statute receives immunity from common law action, while that which does not remains subject to potential liability at common law. This article analyses the adoption of the immunity approach in Australia under the relevant federal industrial relations statutes that have operated since 1993. Commencing with discussion of the hostility of the common law to collective action and the principle of legality, a presumption of statutory interpretation that presumes Parliament would not have abrogated common law rights without an express intention to do so, this article examines how the scope of protected industrial action in Australia has been consistently narrowed through hostile judicial interpretation. Such interpretation has been grounded in an approach which narrows the extent that common law rights are restricted by the statute and construes the statutory enactment of a right to strike as conferring a "privilege" on those industrial actors who remain "worthy" enough to access it. Considering the progressively negative impact on the right to strike of this approach, the argument in this article echoes calls made by Gordon Anderson in 1987 to reject the continued role of the common law in the regulation of industrial action. It is argued that the law of strikes in Australia should be codified. Such an approach should assist in downplaying judicial tendencies to interpret the right to strike as a privilege rather than as a necessary component of a functioning system of voluntary collective bargaining.